Penerapan Model Pembelajaran Jigsaw Untuk Meningkatkan Prestasi Belajar IPA Siswa Kelas V SDN 2 Joanyar - Kadek Eva Susanti; Kadek Juli Firmanita (Pendagogia: Jurnal Pendidikan Dasar, 2021)
This research is classified as action research. Because it is conducted in the classroom, this research is called classroom action research. This study took 25 students who were studying in class V in the first semester of the 2017/2018 academic year at SD Negeri 2 Joanyar. This classroom action research aims to improve science learning achievement by maximizing the application of the Jigsaw Cooperative Model in the implementation of the learning process. The belief that emerged from the beginning was that the use of traditional models used by teachers to achieve day-to-day activities was an obstacle to the expected increase in learning achievement so that researchers chose a more constructive model. After the data was collected using a learning achievement test and analyzed using descriptive analysis, it was found that the increase in student achievement from the initial data was 62.60 in the first cycle, the average increased to 67.76 and in the second cycle it increased again to 75.40 with good learning mastery. initially 44,00% increased to 60,00% in the first cycle and increased to 92.00% in the second cycle. The conclusion that can be drawn from the implementation that has been carried out optimally following the theories of educational experts is that the Jigsaw Type Cooperative model can improve student learning achievement.